Pooled prevalence and determinants of informed choice of contraceptive methods among reproductive age women in Sub-Saharan Africa: A multilevel analysis - Nuhamin Tesfa Tsega; Tsion Tadesse Haile; Melaku Hunie Asratie; Daniel Gashaneh Belay; Daniel Gashaneh Belay; Mastewal Endalew; Fantu Mamo Aragaw; Sintayehu Simie Tsega; Moges Gashaw (Frontiers Media S.A., 2022)
BackgroundDespite the commitments of the government to minimize unintended pregnancy, abortion, and unmet need for contraceptives, as per our search of the literature, there is no study on the pooled prevalence and determinants of informed choice of contraceptive methods in sub-Saharan Africa. Therefore, this study aimed to assess the pooled prevalence and determinants of informed choice of contraceptive methods among reproductive-aged women in sub-Saharan Africa.MethodsThis study was based on the 32 Sub-Saharan African countries Demographic and Health Survey data. A total weighted sample of 65,487 women aged 15-49 was included in the study. The data were cleaned, weighted, and analyzed using STATA Version 14 software. Multilevel logistic regression modeling was used to identify determinants of an informed choice of contraceptive methods. Adjusted odds ratio (AOR) with 95% Confidence Interval (CI) and p-value < 0.05 were used to declare the significant determinants.ResultThe pooled prevalence of informed choice of contraceptive methods among reproductive age (15-49) women in sub-Saharan Africa was 49.47% (95%CI: 44.33, 54.62%) with I2 =99.5%, and variations in range of 19.42 to 78.42%. Women aged 25-34 years old (AOR = 1.26 95%CI: 1.21, 1.32) and 35-49 years (AOR = 1.33 95%CI: 1.27, 1.40), attending primary education (AOR = 1.26, 95% CI: 1.20, 1.32), secondary education (AOR = 1.50, 95% CI: 1.43, 1.58) and higher education (AOR = 2.01, 95% CI: 1.84, 2.19), having media exposure (AOR = 1.12, 95%CI: 1.07, 1.16), utilizing IUD (AOR = 1.98, 95%CI: 1.79, 2.19), injectable (AOR = 1.29, 95%CI: 1.23, 1.36) and implants (AOR = 1.70, 95%CI: 1.61, 1.79), survey year 2016-2020 (AOR = 1.38, 95%CI: 1.31, 1.44), women from lower middle (AOR = 1.25, 95%CI: 1.19, 1.31) and upper middle income level countries (AOR = 1.37, 95%CI: 1.23, 1.53) were associated with increased odds of informed choice of contraceptive methods. While, women who accessed contraceptives from private clinics (AOR = 0.64, 95%CI: 0.61, 0.67), pharmacies (AOR = 0.37, 95%CI: 0.35, 0.40), and others (AOR = 0.47, 95%CI: 0.43, 0.52), women in East Africa (AOR = 0.70, 95% CI: 0.67, 0.73), Central Africa (AOR = 0.52, 95% CI: 0.47, 0.57), and South Africa (AOR = 0.36, 95% CI: 0.32, 0.40) were associated with decreased odds of informed choice of contraceptive methods.ConclusionThe pooled prevalence of informed choice of contraceptive methods in Sub-Saharan Africa is low with high disparities among the countries. Enhancing maternal education and media exposure, providing greater concern for the source of contraceptive methods, and strengthening the economic status of the country are recommended to enhance informed choice of contraceptive methods.